THE LIMITATIONS OF THE EXCULPATORY CRITIQUE: A RESPONSE TO MIKKEL BOLT RASMUSSEN - Kestner, Grant (The Nordic Journal of Aesthetics, 2017)
This essay constitutes a response to Mikkel Bolt Rasmussen’s essay “A Note on Socially Engaged Art Criticism”. In particular, the essay focuses on the concept of an “exculpatory critique”. This term refers to a set of arguments in contemporary art criticism which contend that artistic practices that engage directly with processes of social or political change sacrifice their aesthetic validity while also providing an ideological justification for existing systems of domination. Kester seeks to demonstrate some of the shortcomings involved in this critique by examining the underlying model of political transformation on which it is based and outlining an alternative account of art’s role in social action.